INCREASING STUDENTS’ MOTIVATION THROUGH DIGITAL TECHNOLOGIES: ANALYSIS OF MODERN EDUCATION - Ramazonova Surayyo (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In the contemporary educational landscape, technology has become a fundamental component of foreign language teaching and learning. Its integration into classrooms has transformed traditional pedagogical approaches into more interactive, learner-centered, and flexible systems. This paper aims to explore the multifaceted role of technology in foreign language teaching, focusing on its impact on learners’ motivation, language skills development, and overall learning outcomes. The study also examines the challenges associated with technological integration, including issues related to infrastructure, teacher competence, and overdependence on digital tools. Drawing on existing literature and a small-scale experimental design, the findings suggest that technology significantly enhances language learning when used appropriately. However, it should be viewed as a supportive tool rather than a replacement for teachers.